Acetabular osteophyte formation in dysplastic hip osteoarthritis - Hiroto Funahashi; Yusuke Osawa; Yasuhiko Takegami; Yuto Ozawa; Hiroaki Ido; Takamune Asamoto; Shiro Imagama (BMC Musculoskeletal Disorders)
Abstract The growth of periacetabular osteophytes with developmental dysplasia of the hip (DDH) remains unclear. This study aimed to perform a three-dimensional assessment of periacetabular osteophytes and the effects of superiorization (SP) and lateralization (LT) of the femoral head on osteophyte formation. Female (n = 105) with unilateral hip osteoarthritis due to DDH who underwent total hip arthroplasty between 2016 and 2022 were included. The SP and LT of the femoral head were assessed using anteroposterior radiographs. We measured the periacetabular osteophyte using computed tomography. The correlation coefficient between SP or LT and the length of each osteophyte were investigated. Furthermore, multiple regression analyses with SP and LT as explanatory variables and each osteophyte as an objective variable were performed to evaluate the effect of SP and LT on osteophyte formation. The longest osteophyte was the anterior osteophyte (20.48 mm ± 11.8 mm). Acetabular osteophytes correlated with LT as follows: anterior (r = 0.55), posterosuperior (r = 0.51), and inferior (r = 0.48). Multiple regression analysis showed that all acetabular osteophytes were influenced by LT (p < 0.05 for all factors). Hip surgeons may need to be aware that cases with marked lateralization of the femoral head require treatment of the periacetabular osteophytes.